Eksistensi Play dan Labour dalam Penggunaan In-App Game pada Aplikasi Lokapasar Shopee - Abyzan Syahadin Bagja Dahana (Jurnal Komunikasi dan Kajian Media, 2024)
This study aims to describe the practice of play and labour in the use of in-app games on marketplace applications. Various researchers have viewed in-app games or games within marketplace mobile applications such as Shopee as gamification efforts that have the potential to improve the consumer experience and thus encourage transactions. Nevertheless, gamification within marketplace applications has the potential to blur the boundaries between "play" practices and transform them into "labour" practices. However, there has been no research that reveals the practice of labour disguised by the practice of play in the use of game features in marketplace applications by consumers. This study uses the literature study method and adopts the concept of play and labor to identify play and labor practices that are intertwined with the use of game features in the Shopee mobile application. This study found that the practice of “play” is reflected by Shopee application users, who always feel challenged to continue playing to achieve the awards that the game promises. Shopee application users also engage in social interaction with other users as an implication of the playing process that requires involvement with other individuals. Meanwhile, “labour” practices are reflected in individual playing practices that take place over a certain period of time or frequency, thereby increasing financial benefits for platform owners. Although game users indirectly contribute to providing benefits to the Shopee company, they only get rewards in the form of game prizes whose amount is not commensurate with the total profits that Shopee gets.